Narrowing the gap between museums, classrooms and technology: the U.Openlab Initiative Prototype - M. M. Pinto (2016)
Innovation has a cost. It is often the case that museums trying to innovate, simply cannot afford what ittakes to build truly memorable exhibitions. Lack of human resources and high-tech equipment makesit hard to create quality contents that could be shown to the general public.Nevertheless, universities museums are usually embedded in an environment that has the potential toprovide all the tools and human resources required. The only thing needed is to establish a properstrategy and an interaction facilitator platform - U.OpenLab - which enables creating, building andsharing knowledge about the museums collections and the academic population. This will make iteasier to distribute the aforementioned knowledge to the general public, in a truly sustainable,systematic, integrated and articulated manner.In this paper we are going to present the University of Porto (U.Porto) OpenLab prototype that is beingbuilt as the stepping stone of this project, providing students with learning in a project environment.